Association of violence against women with religion and culture in Erbil Iraq: a cross-sectional study - Al-Tawil Namir Ghanim (BMC, 2012)
Abstract Background Violence against women by intimate partners is still a public health problem. The study aims at finding out the prevalence of violence among women residing in Erbil city (Muslim culture) and in Ankawa sub-district (Christian culture), finding out the role of religion and culture on the prevalence, and finding out some other factors (like occupation of husband and wife, age at marriage, woman agreement for marriage, illegitimate relations of husband) that might be associated with violence. Methods A cross-sectional study was carried out in Erbil during the second half of the year 2011. Two groups were considered; group one (G1) included women residing in Ankawa sub-district (representing Christian culture), and group two (G2) included women residing in Erbil city (representing Muslim culture). A convenience method of sampling was used to collect the sample (250 women of each group). Questionnaire was designed to collect information about history of exposure to physical, sexual, and psychological violence, in addition to the related factors. These forms were distributed (by women of the Assyrian Women Union) in sealed envelopes to women attending the Mass in three churches located in Ankawa. Women of Erbil group were recruited from the maternity teaching hospital of Erbil. The same questionnaire was distributed to them by the same team. Binary logistic regression was used to show the independent effect of each factor on the prevalence of violence. Results Overall prevalence of violence (physical and/or sexual) in G2 (20.8%) was higher than that of G1 (18.8%). The prevalence of psychological violence was 40% in Erbil, which was significantly higher than the prevalence (24.8%) of Ankawa. The rates of physical and sexual violence were also higher in Erbil (18.4%, and 10.8% respectively) than rates of Ankawa (16.8% and 8% respectively). Factors found to be significantly associated with overall violence were: culture of Erbil, alcoholic husband, wife working as manual worker (compared with professionals), and having children. Conclusion Violence against women is a serious public health issue. There was significant role of culture on the prevalence of violence.